2019
DOI: 10.1200/jco.2019.37.8_suppl.tps129
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative PD1 checkpoint blockade and receptor activator of NFkB ligand (RANKL) inhibition in non-small cell lung cancer (NSCLC) (POPCORN).

Abstract: TPS129 Background: Preclinical studies indicate Receptor Activator of NF-κB Ligand (RANKL) blockade improves anti-tumor efficacy of immune checkpoint blockade (ICB). Clinical trials combining denosumab (anti-RANKL mAb) with ICB are underway in various cancers although the hypothesized mechanism of action of such combinations remains incomplete. RANKL and its receptor, RANK, are frequently expressed in NSCLC (tumor and immune cells). Denosumab demonstrated survival advantage over bisphosphonate in metastatic N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some immunotherapies have been utilized to leverage the immune system to fight tumors (Kobold et al, 2018;Popovic et al, 2018). Immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1, have emerged as an effective therapeutic selection for advanced breast cancer, metastatic melanoma and NSCLC (Wang et al, 2018;Ahern et al, 2019;Liu D. et al, 2019). NSCLC is characterized by several mutations in the immune system, making it possible that these patients may benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Some immunotherapies have been utilized to leverage the immune system to fight tumors (Kobold et al, 2018;Popovic et al, 2018). Immune checkpoint inhibitors (ICIs), such as anti-PD-1/PD-L1, have emerged as an effective therapeutic selection for advanced breast cancer, metastatic melanoma and NSCLC (Wang et al, 2018;Ahern et al, 2019;Liu D. et al, 2019). NSCLC is characterized by several mutations in the immune system, making it possible that these patients may benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of the combination in clinical practice was reported in the CHARLI trial, a phase I/II study of the effect of denosumab with nivolumab (an anti-PD-1), with or without ipilimumab (anti-CTLA4), in patients with metastatic melanoma, which showed that the combination is safe and with at least interesting response rates (42). Pembrolizumab and denosumab have also been tested in clear cell renal cell carcinoma, a phase II trial (KeyPAD trial) with response rates close to 31% (43), and there are other ongoing trials with ICI in different tumors such as in lung cancer (Popcorn Trial) (44). Testing the combination in BC will be of interest, although we recognize that more data are required.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining genes, Chen et al [40] found that CCNB2 could serve as a marker to predict response to anti-PD-1 therapy in NSCLC patients, suggesting that CCNB2 might also be a predictor of response to anti-PD-1 treatment in melanoma. For another important gene TNFRSF11A, also named RANK, a clinical trial combining its monoclonal antibody and Immune checkpoint inhibitors for the treatment of melanoma were already underway [41]. The other genes such as IFNA13, ACTG1 and PPP2R1B all involved in immune-regulatory activities, playing distinctive roles in melanoma cells' focal adhesion and motility [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%